Improving The Quality Of Eye Care Services Using The Servqual Method, Importance–Performance Analysis, And The 5 Whys Analysis (Case Study: Abc Eye Clinic) - Fiona Rahmi Alikaputri (Eduvest - Journal of Universal Studies, 2026)
The presence of visual disturbances in the eye can cause productivity decrease because visual information cannot be captured properly. East Java is a province with a high rate of visual impairment in Indonesia, indicating the high incidence in the region so that affordable eye health services are needed. ABC Eye Clinic is an eye clinic located in East Java which has several complaints from patients, including the need to improve public facilities, not distinguishing between general patients and BPJS, length of service time, doctors not arriving on time and website activation for the latest information. Therefore, this study was conducted with the aim of identifying service gaps and critical attributes of services at the ABC Eye Clinic. The research started with a field study and distributed questionnaires containing 20 (twenty) service attributes. Followed by the calculation of the service gap to determine the gap and mapping Importance - Performance Analysis to determine the critical attributes. Importance – Performance Analysis produces critical attributes that are the basis for developing root cause finding using 5 Whys Analysis. The root cause of the 5 Whys Analysis was developed into 4 (four) alternative recommendations for improvement, including the development of a means to accommodate criticism and suggestions, divide the parking lots and the implementation of valet parking, development of patient data information systems, and development of job descriptions and job specifications.